Cytotoxicity and apoptosis induction of Ardisia crispa and its solvent partitions against Mus musculus mammary carcinoma cell line (4T1) - Nordin, Muhammad Luqman; Kadir, Arifah Abdul; Zakaria, Zainul Amiruddin; Othman, Fauziah; Abdullah, Rasedee; Abdullah, Muhammad Nazrul Hakim (Hindawi Publishing Corporation, 2017)
This study was conducted to investigate the cytotoxicity and apoptosis effect of A. crispa extract and its solvent partition (ethyl acetate and aqueous extract) against Mus musculus mammary carcinoma cell line (4T1). The normal mouse fibroblast cell line (NIH3T3) was used as comparison for selective cytotoxicity properties. The cytotoxicity evaluation was assessed using MTT assay. AO/PI dual fluorescent staining assay and Annexin V-FITC were used for apoptosis analysis. Results showed that 80% methanol extract from leaves showed most promising antimammary cancer agent with IC50 value of 42.26 ± 1.82 μg/mL and selective index (SI) value of 10.22. Ethyl acetate was cytotoxic for both cancer and normal cell while aqueous extract exhibited poor cytotoxic effect. 4T1 cells labelled with AO/PI and Annexin V-FITC and treated with 80% methanol extract demonstrated that the extract induces apoptosis to 4T1 mammary cancer cells. In conclusion, 80% methanol extract of A. crispa was selectively cytotoxic towards 4T1 cells but less cytotoxic towards NIH3T3 cells and induced the cancerous cells into apoptotic stage as early as 6 hours.